PENGARUH KOMBINASI ZIG-ZAG EXERCISE DAN T-DRILL EXERCISE TERHADAP TINGKAT KELINCAHAN PADA PEMAIN FUTSAL - Fidelis Pratama; Nurul Halimah; Sartoyo Sartoyo; Angria Pradita (Kieraha Medical Journal, 2026)
Futsal is played in a confined space at high intensity; consequently, agility is a crucial physical attribute that enables players to change direction rapidly without losing their balance. Many school-level players have not yet undergone specific training programs focused on changing direction. This study aimed to analyze the effect of a combined intervention consisting of Zig-zag exercises and T-Drill exercises on improving the agility levels of futsal players. This quantitative study employed a pre-experimental design (one-group pretest-posttest) involving 16 players from the futsal extracurricular program at SMAN 2 Malang City. Participants were selected via purposive sampling based on the following criteria: male, aged 15–18 years, and in good physical health. Exclusion criteria included players with injuries and those unwilling to participate. The combined training intervention was administered twice weekly over a four-week period. Agility was measured using the Illinois Agility Test, timed with a digital stopwatch. Data normality was assessed using the Shapiro-Wilk test, and analysis was conducted using the Paired Sample T-Test. The results demonstrated a highly significant improvement in agility across all subjects. The mean completion time for the Illinois Agility Test was 18.67 seconds at pre-test and decreased to 17.04 seconds at post-test, with a p-value of 0.000 (p < 0.05). The combined Zig-zag and T-Drill exercise program proved to have a significant effect on enhancing the agility of futsal players.